Analysis of Sanctions Imposed on Foreign Nationals Violating Article 71 Letter A in Conjunction with Article 116 of Law Number 6 of 2011 on Immigration - Hamdi, Muhammad Arief; Difa, Aulia Diantama; Santiago, Faisal; Wiraputra, Anindito Rizki (Faculty of Law, Universitas Pekalongan, 2024)
Ideally, foreign nationals who have entered and settled in Indonesia are required to provide information regarding their identity and family, as well as report any changes in marital status, nationality, employment, sponsorship, and address to the immigration office. This reporting obligation can be fulfilled by the sponsor; however, if the sponsor fails to do so, the foreign national bears the responsibility of reporting it. The failure of many foreign nationals to report these changes has led to various violations in Indonesia. As a country that adheres to Pancasila as the foundation of national life, Indonesia strives to maintain a balance between legal certainty, justice, and the welfare of its citizens. To achieve these three aspects, legal norms are required to regulate people's behavior, ensuring order and societal stability for the prosperity of the nation. However, in its enforcement, there is a disparity in authority among various immigration officials in Indonesia. Therefore, this study analyzes legal aspects of sanction imposition and explores possible solutions to this issue to create harmonization of immigration law in Indonesia. This research also refers to comparative studies with several other countries to provide a broader perspective on immigration law enforcement worldwide. This study employs a qualitative research approach, as described by Creswell. To address the research problems and propose appropriate solutions, the author applies the Dignified Justice Theory, which aligns with Indonesia’s national philosophy Pancasila.